(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2024)
Background: There are various reports regarding the suicide commission by HIV positive persons, but as such postmortem serological studies are yet not done to document the status in autopsy. Also it’s vital to test a body before autopsy to avoid infection to the forensic experts and concerned persons in autopsy and allied work. Objectives: The objective of the study was to estimate the prevalence of HIV infection, in unreported post-mortem cases in the autopsy room. Material and Methods: The prospective study was done at the Department of Forensic Medicine in collaboration with the Department of Microbiology located in the Tertiary Care Government Hospital, Mumbai. Total of 216 cases were examined during a span of one year. Cases selected as per inclusion and exclusion criteria, tested for HIV after taking consent from guardians. Results: Most common age group was found to be 31-40 years. Males were 72.22% while females were 27.78% of study. Out of total 6 were tested positive for HIV. Out of total 6 HIV cases 4 (80%) were males and 2 (20%) were females. Out of 6 cases 5 (83.3%) were below 50 yrs. 82.3% tested positive in first 24 hours of death. 3 (50%) died due to pulmonary tuberculosis, 2 (33.3%) due to meningitis and 1 (16.7%) due to lobar pneumonia. Conclusions: HIV among dead bodies presenting to autopsy is not uncommon.